Modulating macrophage function to reinforce host innate resistance against Mycobacterium avium complex infection - Park, Hyun-Eui; Lee, Wonsik; Choi, Sangwon; Jung, Myunghwan; Shin, Min-Kyoung; Shin, Sung Jae (Frontiers in Immunology, 2022)
Mycobacterium avium complex (MAC) is the main causative agent of infectious diseases in humans among nontuberculous mycobacteria (NTM) that are ubiquitous organisms found in environmental media such as soil as well as in domestic and natural waters. MAC is a primary causative agent of NTM-lung disease that threaten immunocompromised or structural lung disease patients. The incidence and the prevalence of M. tuberculosis infection have been reduced, while MAC infections and mortality rates have increased, making it a cause of global health concern. The emergence of drug resistance and the side effects of long-term drug use have led to a poor outcome of treatment regimens against MAC infections. Therefore, the development of host-directed therapy (HDT) has recently gained interest, aiming to accelerate mycobacterial clearance and reversing lung damage by employing the immune system using a novel adjuvant strategy to improve the clinical outcome of MAC infection. Therefore, in this review, we discuss the innate immune responses that contribute to MAC infection focusing on macrophages, chief innate immune cells, and host susceptibility factors in patients. We also discuss potential HDTs that can act on the signaling pathway of macrophages, thereby contributing to antimycobacterial activity as a part of the innate immune response during MAC infection. Furthermore, this review provides new insights into MAC infection control that modulates and enhances macrophage function, promoting host antimicrobial activity in response to potential HDTs and thus presenting a deeper understanding of the interactions between macrophages and MACs during infection.